Studi Kasus Asuhan Kebidanan Komprehensif (Jurnal Kesehatan Siliwangi, 2021)
During pregnancy care, there were Braxton Hicks discomfort was found at 38-39 weeks of gestation, problems with irregular consumption of iron supplements and other mineral as well as discrepancies in maternal weight gain during pregnancy based on BMI category. As the fetus grows, the ligaments will stretch, making it easier to strain, which can lead to Braxton Hicks. According to Varney's theory in 2019 to overcome the discomfort of Braxton Hicks can be done by changing body position / body mechanics, relaxation techniques, and pregnancy exercises to stretch the muscles. Pregnancy, childbirth, postpartum and newborn care based on midwifery management and midwifery care standards, the problem has been resolved. There is a difference between theory and practice, weight gain of the mother during pregnancy less than WHO standards, giving vitamin A supplements and antibiotics to postpartum mothers and repatriate mother and baby under 24 hours after delivery. It is expected that students will further improve their competence in providing comprehensive, early care and counseling and can provide comprehensive care for each patient they care for.